The property functions of whiteness and Swedishness – a case study of race reputation and status in urban education - Osa Lundberg (Nordic Journal of Studies in Educational Policy, 2021)
This paper examines the property functions of whiteness in urban educational practices in Sweden. Whiteness can be understood as racial privilege and racialized knowledge. Cheryl Harris’ theory on whiteness as property is applied in order to discuss critical incidences in the pedagogical discourse in which whiteness functions as a form of property in terms of reputation and status related to Swedishness and the right to use and enjoy public spaces. The analysis is drawn from ethnographic data from a study of ninth grade students and teachers at an urban compulsory school in Sweden. The results show that the status of Swedish is racialized and remains elusive to students of colour, whereby entitlements to take part in, use and enjoy Swedish society are truncated by the premise of white normativity.